Knowledge and attitudes of patients' attending the diabetic Clinic, General Hospital Kandy, about their disease and its control - Bandara, K.M.G.K (My University, 2001)
Study showed that significant statistical difference on positive attitudes between different sex(p=0.04). different income group (p=0.000) and respondents with family history and without family history of diabetes mellitus ( p=0.003). But there was no significant statistical difference in median attitudinal scores between age groups, with number of children they have and marital status